Exploring Teachers' and Students' Perceptions on Collaborative Learning Implementation at Eleven Grade of SMA Tri Sukses - Siska Aulia; Harpain, Harpain (Jurnal Multidisiplin Indonesia, 2024)
This study explores the perceptions of teachers and students regarding collaborative learning in Grade Eleven at SMA Tri Sukses. Using a qualitative design, the research involved 32 students from class XI M2, with data collected through questionnaires and interviews. The findings revealed that 55% of students felt collaborative learning facilitated the exchange of ideas, supporting critical thinking and communication skills. However, some students expressed concerns about the method’s effectiveness in helping them master the material, with 52% remaining neutral on the comfort of working in groups. These results highlight the benefits of collaborative learning in enhancing discussions, teacher-student communication, and peer interaction, while also emphasizing the importance of managing group dynamics to ensure comfort and support for all students. The study offers valuable insights for educators aiming to improve collaborative learning strategies in secondary education.